Дочь колдуньи: роман / Кэтлин Кент - Кент Кэтлин (Азбука, 2012)
Экземпляры: Ф. 8 (20200708) / Инвентарный номер: 43483 / Цена: 264.99 / Сис.шифр: 84(7Сое) / Авт.знак: К 35 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)